2018
DOI: 10.3390/ijms19113490
|View full text |Cite
|
Sign up to set email alerts
|

Defined Small Molecules Produced by Himalayan Medicinal Plants Display Immunomodulatory Properties

Abstract: Plant-derived compounds that modulate the immune responses are emerging as frontline treatment agents for cancer, infectious diseases and autoimmunity. Herein we have isolated 40 phytochemicals from five Bhutanese Sowa Rigpa medicinal plants—Aconitum laciniatum, Ajania nubegina, Corydalis crispa, Corydalis dubia and Pleurospermum amabile—and tested 14 purified compounds for their immunomodulatory properties using a murine dendritic cell (DC) line, and cytotoxicity against a human cholangiocyte cell line using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 62 publications
(98 reference statements)
0
15
0
Order By: Relevance
“…Kiran 23 have already reported the phytoconstituents of Siddha formulation KSK. These compounds have been detailed of their biological activities; some of them were found to have thrombolytic, immunomodulatory, anti-inflammatory, and fibrinolytic activity, for example, β-bisabolene, 48-51 piperine, [52][53][54] Squalene 55,56 Chebulagic acid, 57 Carvacrol, 58,59 Luteolin 60,61 Magnoflorine. [62][63][64] As per Siddha, stickiness, mucilaginous, rounded, little hard are listed as characters of Aiyam.…”
Section: Resultsmentioning
confidence: 99%
“…Kiran 23 have already reported the phytoconstituents of Siddha formulation KSK. These compounds have been detailed of their biological activities; some of them were found to have thrombolytic, immunomodulatory, anti-inflammatory, and fibrinolytic activity, for example, β-bisabolene, 48-51 piperine, [52][53][54] Squalene 55,56 Chebulagic acid, 57 Carvacrol, 58,59 Luteolin 60,61 Magnoflorine. [62][63][64] As per Siddha, stickiness, mucilaginous, rounded, little hard are listed as characters of Aiyam.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that flavonoids have many beneficial pharmacological and biological functions, such as antioxidant, anticoagulant, immunomodulatory, anti-inflammatory, anti-microbial, etc. [ 41 , 46 ]. However, some types of flavonoids showed cytotoxicity against normal healthy cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, some types of flavonoids showed cytotoxicity against normal healthy cells. Wangchuk et al [ 46 ] reported that luteolin exhibited considerable cytotoxicity on a human normal cholangiocyte cell line. Kae, quercetin and isoquercitrin showed hemolytic potential on human erythrocytes [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The traditional purification methods such as silica gel column chromatography [6, 1214], flash chromatography [15, 16], and GC/GC‐MS [6] have been reported for various Pleurospermum species. However, P. candollei has not been so far investigated for phytochemical investigation.…”
Section: Introductionmentioning
confidence: 99%